2016
DOI: 10.1007/s10439-016-1566-x
|View full text |Cite
|
Sign up to set email alerts
|

Design of pH-Responsive Biomaterials to Enable the Oral Route of Hematological Factor IX

Abstract: The oral administration of hematological factor IX can offer a convenient prophylactic treatment for hemophilia B patients. pH-Responsive hydrogels based on poly(methacrylic acid)-grafted-poly(ethylene glycol) (P(MAA-g-EG)) have been engineered as delivery vehicles for factor IX. In oral delivery, such hydrogel carriers protected factor IX from the gastric environment and released it under intestinal conditions as demonstrated by evaluation of the loading and release of factor IX. Tailoring of the hydrogel net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
2
12
1
Order By: Relevance
“…At 5 mg mL −1 , a decrease in relative cellular proliferation occurs for all formulations. These results agree with the published results showing that when incubated with HT29‐MTX cells for 6 hours, P(MAA‐g‐EG) hydrogel formulations do not induce cytotoxicity up to a concentration of 5 mg mL −1 …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…At 5 mg mL −1 , a decrease in relative cellular proliferation occurs for all formulations. These results agree with the published results showing that when incubated with HT29‐MTX cells for 6 hours, P(MAA‐g‐EG) hydrogel formulations do not induce cytotoxicity up to a concentration of 5 mg mL −1 …”
Section: Resultssupporting
confidence: 93%
“…The reported Q values in Figure A for 1% PEGDMA400 and 1.25% PEGDMA400 were obtained by collecting remaining hydrogel pieces, which shows a similar decrease in Q and increase in v 2,s with increasing cross‐linking density ( Q 1P = 27 > Q 125P = 16, v 2,s1P = 0.04 < v 2,s125P = 0.068). However, the swelling ratios for the 1% TEGDMA were greater than 1% PEGDMA, which was not in agreement with the previous reports which show that increasing cross‐linking length increases the swelling capacity of both P(MAA‐ co ‐NVP) and P(MAA‐g‐EG) hydrogels . This is likely due to gel rupture and subsequent mass loss.…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, these results did not agree with equilibrium swelling results, which indicated that longer PEG length led to a greater swelling capacity. This swelling capacity results in larger pores being opened in the hydrogel matrix, which should facilitate greater protein loading efficiency . This difference may be attributed to the fact that the PEG5000 hydrogels contain a greater incorporation of MAA and thus a more negatively charged backbone and increased electrostatic repulsion between the backbone and the negatively charged protein species, inhibiting the loading potential of the microparticles .…”
Section: Discussionmentioning
confidence: 99%
“…33 This difference may be attributed to the fact that the PEG5000 hydrogels contain a greater incorporation of MAA and thus a more negatively charged backbone and increased electrostatic repulsion between the backbone and the negatively charged protein species, inhibiting the loading potential of the microparticles. 9,27,33 Interestingly, studies performed with the P(MAA-g-EG) copolymer system found that increasing the PEG length, but maintaining the same incorporation density, resulted in decreased diffusion of a variety of tested protein therapeutics into the hydrogel matrix. 25,34 This behavior was attributed to the longer PEG chains dangling into the polymer mesh space and obstructing protein diffusion.…”
Section: Discussionmentioning
confidence: 99%